Nanomaterials in agricultural applications. Recent advances in the banana industry. - Araya-Mattey, Jorge (2024)
The application of nanotechnology in agriculture has been reflected in a considerable number of scientific contributions that show a potential interest in the development of new products that includes soil care, fruits and crops, to the improvement in the formulations of fertilizers, stimulating pesticides and plant growth regulators. Product of an exhaustive bibliographic revision, concepts, properties and advantage of nanostructured systems applied in agricultural production systems in different countries of America, Asia and Africa is described. It is explore, the recent development in release profile of natural and synthetic bioactive compounds, with an adequate and programmed specificity of the encapsulated compounds by using natural and synthetic matrices on plants. Moreover, it is discussed the effects and of addition of nanomaterials on plants and the environment. Finally, the use and challenges about nanotechnology strategies on banana crops is presented.